1973
DOI: 10.1002/eji.1830030302
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the transforming lymphocyte in chronic lymphocytic leukemia

Abstract: The nature of the transforming lymphocyte in chronic lymphocytic leukemia * Lymphocyte transformation in vitro was studied with lymphocytes from patients with chronic lymphocytic leukemia (CLL). The responding capacity t o phytohemagglutinin (PHA), pokeweed mitogen (PWM) and allogeneic lymphocytes, as well as the stimulating capacity in mixed lymphocyte cultures (MLC), were assessed.Lymphocytes of CLL patients display a depressed and delayed reaction t o PHA. In MLC experiments a decreased responding and stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies of the MLR stimulatory capacities of CLL lymphocytes have reported both normal (25)(26)(27) and decreased stimulatory capacity (28,29). However, it is apparent in all of the studies that when the data are recalculated on a per B-cell basis, the MLR generated by CLL subjects are abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the MLR stimulatory capacities of CLL lymphocytes have reported both normal (25)(26)(27) and decreased stimulatory capacity (28,29). However, it is apparent in all of the studies that when the data are recalculated on a per B-cell basis, the MLR generated by CLL subjects are abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the findings are consistent with the view of Schweitzer et a1. 28 and of Wybran et a1.33 that the circulating T cells in typical cases of C.L.L. represent a normal subpopulation diluted in a large excess of neoplastic B lymphocytes.…”
Section: Discussionmentioning
confidence: 93%
“…In vitro proliferation of lymphocytes in response to stimulation with lectins, anti-lymphocyte serum (ALS), allogeneic cells (MLR), and Candida antigen was assayed as described by Schweitzer et al (25) and DuBois et al (26). Cultures in triplicate were performed in microtiter plates.…”
Section: Cell-mediated Immunitymentioning
confidence: 99%